La honestidad en política. Niklas Luhmann - Luhmann, Niklas (Madrid, España : ARCE, 1996)
Hace un análisis acerca de los problemas morales asociados al arte de gobernar
Keywords: TEORIA POLITICA; PODER; ETICA; NORMAS